Exploring Risk Aspects in Public-Private Partnership Infrastructure Research: A Bibliometric Analysis - Sunandar, Ali; Abd Karim, Saipol Bari; Zolkafli, Umi Kalsum (PT Penjaminan Infrastruktur Indonesia (Persero), 2024)
The risk aspect is a key component of the Public-Private Partnership (PPP) infrastructure scheme. The study employed bibliometric analysis to shed light on research trends concerning risk aspects in PPP. The author focused on publication trends, co-authorship networks, local citation patterns, cluster analysis, and co-occurrence of key terms. In addition, the authors compiled a list of studies on the risk aspects of PPP infrastructure. Using bibliometric data from 356 Scopus-indexed publications, this study identifies the leading authors, nations, institutions, publishers, influential papers, and research topics related PPP infrastructure risk over the past decade (2014-2023). The findings reveal that from 2014 to 2017, research predominantly focused on risk factors, success criteria, development projects, contracts, toll roads, water supply, and social infrastructure. Between 2018 and 2020, the emphasis shifted towards risk assessment, risk analysis, risk management, and risk allocation. Since 2021, the research trends have evolved to include urban growth, investment, the private sector, partnership models, internet protocols, and intelligent systems. Future research on PPP infrastructure risk should incorporate technological concepts and business entity perspectives. This study also contextualizes its findings within the broader landscape of emerging markets in Asia and globally and highlights these trends in the Indonesian context.